2021
DOI: 10.3390/toxics9120335
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Organophosphate Metabolites and Metabolic Biomarkers of Conventional and Organic Farmers in Thailand

Abstract: Organophosphate (OP) pesticides are used by most farmers to remove insects and to increase productivity; however, questions remain on the long-term health impacts of their use. This study assessed the relationship between OP biomarker levels and metabolic biomarker parameters. Conventional farmers (n = 213) and organic farmers (n = 225) were recruited, interviewed, and had physical health examinations. Serum glucose and lipid profiles, triglycerides, total cholesterol, high-density lipoproteins (HDL), and low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(38 reference statements)
2
2
0
Order By: Relevance
“…In addition, that DMP, DEP, and DETP metabolite levels detected in the present study were higher among the agricultural laborers as compared with other workers is consistent with earlier reported studies 39 . In the present study, higher mean concentrations of DMP, DEP, and DEDTP were observed among farmworkers storing the pesticides in their houses as compared with those storing in farm is in agreement with earlier reported studies, highlighting not only the effect of long-term exposure to pesticides and but also the nonadoption of GAPs by way of showing higher DAP metabolite levels 23,46 …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, that DMP, DEP, and DETP metabolite levels detected in the present study were higher among the agricultural laborers as compared with other workers is consistent with earlier reported studies 39 . In the present study, higher mean concentrations of DMP, DEP, and DEDTP were observed among farmworkers storing the pesticides in their houses as compared with those storing in farm is in agreement with earlier reported studies, highlighting not only the effect of long-term exposure to pesticides and but also the nonadoption of GAPs by way of showing higher DAP metabolite levels 23,46 …”
Section: Discussionsupporting
confidence: 93%
“…In the present investigation, farmworkers not using PPE showed that detectable levels of at least one DAP metabolite in urine are consistent with other studies conducted elsewhere 42,43 . Further, in the present investigation, DMP was the most frequently detected metabolite (100%) at the highest concentration level (74.91 μg · L −1 ; 17.616 μg · g −1 creatinine) followed by DETP (88%) and DEDTP (82%) among farmworkers when they have not used PPE, which are in line with previous studies' findings among farmworkers with minimal formal education and with low knowledge score on pesticide use 3–5,39,44–46 . Further, the duration of involvement in various agricultural activities and handling pesticides could be an important factor of exposure.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The majority of studies in Thailand reported urinary dialkyl phosphate (DAP) metabolite levels which is a biomarker of organophosphate exposure. Recent studies in Thailand, farmers in all regions of Thailand had urine DAP levels that ranged from 87.32 to 122.2 microgram/gram creatinine (8)(9)(10). Additionally, the study by Suntudrob et al (11) monitored pesticide residues in vegetables from all provinces of Thailand, and reported that 22.3% of the samples had detectable pesticide residues with a range of <0.01-5.9 mg/kg.…”
Section: Introductionmentioning
confidence: 99%